Butadienyl Diiron Complexes: Nonplanar Metalla‐Aromatics Involving σ‐Type Orbital Overlap. (24th August 2020) - Yu, Chao; Zhong, Mingdong; Zhang, Yongliang; Wei, Junnian; Ma, Wangyang; Zhang, Wen‐Xiong; Ye, Shengfa; Xi, Zhenfeng
Abstract: A new class of nonplanar metalla‐aromatics, diiron complexes bridged by a 1, 3‐butadienyl dianionic ligand, were synthesized in high yields from dilithio reagents and two equivalents of FeBr2 . The complexes consist of two antiferromagnetically coupled high‐spin Fe II centers, as revealed by magnetometry, Mössbauer spectroscopy, and DFT calculations. Furthermore, experimental (X‐ray structural analysis) and theoretical analyses (NICS, ICSS, AICD, MOs) suggest that the complexes are aromatic. Remarkably, this nonplanar metalla‐aromaticity is achieved by an uncommon σ‐type overlap between the ligand p and metal d orbitals, in sharp contrast to the intensively studied planar aromatic systems featuring delocalized π‐type bonding. Specifically, the σ‐type interaction between the two Fe 3d xz orbitals and the butadienyl π orbital results in the formation of a six‐electron conjugated system and hence enables the aromatic character. Abstract : A butadienyl bridge and two antiferromagnetically coupled high‐spin Fe II ions unite to form a nonplanar metalla‐aromatic molecule. A σ‐type overlap between the two Fe 3d xz orbitals and the π orbital of the butadienyl ligand makes the six‐electron‐conjugated system aromatic.